The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1097/wox.0b013e3181fc7fa1
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Preschool Wheezing: To Label As Asthma?

Abstract: Asthma is considered a chronic disease, but not all preschool wheezing is asthma since most will eventually grow out of their symptoms. Although still a matter of debate, preschool wheezing can be classified in 2 major groups: virus-induced wheezing and multitrigger wheezing, having a different prognosis and a different treatment approach. Virus-induced wheezing is the most common phenotype of preschool wheezing and is usually associated with a good prognosis. Treatment should be conservative, but if preventiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Meanwhile, in adults, participants worried about conditions such as COPD, echoing widely expressed views. 2022 Contemporary understanding of ‘the asthmas’ is moving towards considering asthma as an initial description, which is then refined into phenotypes with different disease trajectories, and underlying airway inflammation. 23,24 The future of asthma diagnosis (at least in resource-rich settings) may therefore move away from the label of ‘asthma’ to delineating phenotypes or ‘treatable traits’ requiring additional tests (such as FeNO).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in adults, participants worried about conditions such as COPD, echoing widely expressed views. 2022 Contemporary understanding of ‘the asthmas’ is moving towards considering asthma as an initial description, which is then refined into phenotypes with different disease trajectories, and underlying airway inflammation. 23,24 The future of asthma diagnosis (at least in resource-rich settings) may therefore move away from the label of ‘asthma’ to delineating phenotypes or ‘treatable traits’ requiring additional tests (such as FeNO).…”
Section: Discussionmentioning
confidence: 99%
“…However, not all cases of early life wheezing will progress into asthma later on. Most children will eventually grow out of the symptoms and will never develop asthma [ 23 ]. Regardless, as some trials have indicated an increased risk of wheezing/asthma, more data are needed to evaluate this potentially harmful effect of using probiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Though some researchers have used a modified version of the ISAAC questionnaire adapted to the preschool age and study setting [ 28 ], its validity is not well researched. Furthermore, the present study did not consider preschool wheezing as the same entity as asthma as there is lack of chronicity which is expected in asthma [ 6 ]. Moreover, inflammatory reactions in preschool aged children have been shown to be different from those observed in older children with diagnosed asthma [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…As there is an observed increase in prevalence in areas where prevalence was previously low, the global burden of asthma and wheezing, however, continues to increase [ 1 3 ]; with the most significant increase noted among children between one to five years [ 4 , 5 ]. Due to difficulties in demonstrating airflow limitation [ 6 , 7 ] in young children, it is recommended to avoid the term ‘asthma’ in preschoolers with wheezing and airway inflammatory reactions and to use the term ‘wheezing illnesses’ instead [ 6 , 8 ]. Wheezing illnesses affect the health, wellbeing and quality of life of the affected, impose a substantial burden on the family and the healthcare system, and can be particularly troublesome to diagnose and treat, especially when occurring in younger children [ 9 – 12 ].…”
Section: Introductionmentioning
confidence: 99%